2022
DOI: 10.3389/fmicb.2022.908326
|View full text |Cite
|
Sign up to set email alerts
|

Different feeding strategies can affect growth performance and rumen functions in Gangba sheep as revealed by integrated transcriptome and microbiome analyses

Abstract: Due to the harsh environment in the Tibetan Plateau, traditional grazing greatly limits the growth potential of local animals and causes severe ecosystem degradation. This is an urgent issue to be solved, which requires alternative strategies for grazing animals in the Tibetan alpine pastoral livestock systems. This study aimed to investigate the effects of different feeding strategies on growth performance and ruminal microbiota-host interactions in the local breed of sheep (Gangba sheep). Thirty 9-month old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Firmicutes members play an important role in energy conversion, and the ratio of Firmicutes to Bacteroidetes in ruminants is strongly related to animal obesity and body fat storage ( 46 , 47 ). The variation in the microbial biota, directly related to available forage and forage quality, has been recorded in other herbivores grazing on the grassland ( 2 , 23 ). Under grazing conditions, Tibetan sheep need to consume their own energy to survive in a relatively harsh environment, while the barn environment is relatively comfortable and the range of activities is limited, thereby reducing energy consumption and helping to alleviate the phenomenon of fat loss.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Firmicutes members play an important role in energy conversion, and the ratio of Firmicutes to Bacteroidetes in ruminants is strongly related to animal obesity and body fat storage ( 46 , 47 ). The variation in the microbial biota, directly related to available forage and forage quality, has been recorded in other herbivores grazing on the grassland ( 2 , 23 ). Under grazing conditions, Tibetan sheep need to consume their own energy to survive in a relatively harsh environment, while the barn environment is relatively comfortable and the range of activities is limited, thereby reducing energy consumption and helping to alleviate the phenomenon of fat loss.…”
Section: Discussionmentioning
confidence: 86%
“…As such, feeding strategy choice may provide a unique opportunity to manipulate the complex microbial ecosystem ( 22 ). Studies have demonstrated distinct rumen fermentation patterns of sheep switched from natural grazing to indoor feed depending on the feeding strategies (i.e., semigrazing with supplementation or barn feeding) ( 23 ). This difference in feeding strategies resulted in major changes in the nutrients ingested, especially fiber, water-soluble carbohydrates, and starch, and this also affected ruminants’ feed intake and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is no previous report of a relationship found between K00655 and butyrate, but interestingly, this KO was the one with the strongest negative correlation with a microbial genus, F082, which is a member of the order Bacteroidales. This genus also had a slight negative correlation with n-butyric acid and no significant correlation with propionic acid, although Bacteroidales F082 is considered a propionate producer in rumen ( 77 ), but its role in intestinal fermentation is not well defined yet.…”
Section: Discussionmentioning
confidence: 99%
“…The dairy industry is an indispensable part of the national economy and is mainly based on natural grazing, semi-grazing and intensive farming. In the natural grazing and semi-grazing systems, due to the uncertainty of the ecosystem and environment, the DMI is low and ADF content is high in the diet, which reduces the efficiency of nutrient intake or absorption, and individual productivity cannot be fully developed [1]. Under foragebased livestock production systems, the quality and availability of feed determine the later growth and development of dairy cows [2].…”
Section: Introductionmentioning
confidence: 99%